Health-Seeking Behavior and Community Perception of Chhaupadi Practices - Awal, Ganga Laxmi; Techato, Kuaanan; Gyawali, Saroj; Dahal, Bishnu Prasad; Malakar, Indra Mali (Journal of Nepal Health Research Council, 2024)
Background: The Chhaupadi system, mainly in the Western part of Nepal, forces women and girls to stay in huts or cowsheds during menstruation, barring them from their homes. This study aims to analyze the health-seeking behavior and community perception of Chhaupadi practices and examine their relationship with ecology in Tanjakot Rural Municipality of Humla District, Nepal. Methods: A mixed methods design employed ethnography with extended participation in daily lives for data collection through participant observation, field visits, FGD, KII, and non-participation observation. Purposively, Tanjakot Rural Municipality in Humla district, known for its high Chhaupadi practice, was chosen with 143 girls and women aged 18-49 who had experienced menstruation and stayed in Chhau goth. Results: This study found that 97.9% altered their food habit during the mensuration period. The weighted average of 3.94 and standard deviation of 0.32 evidenced the low consumption of inclusion food in menstruation time. Some women were found consuming contraceptive pills to suppress menstruation for ritual participation and water fetching. During menstruation, 70.6% stayed in tents, noting these places were unsafe, especially among the less literate (9.1%) compared to the literate (7.0%), and used cloth as a means during menstruation time. Most of them in the present time seek medical care at health posts (95.8%) during illness, contrasting with historically depended on traditional healers (6.3%) or no treatment (35.7%). Many participants (65.0%) perceived an ecological link to Chhaupadi, and nearly half (49.0%) considered menstruation natural and not sinful (76.9%). Conclusions: The study highlights significant changes in menstruation practices, with reduced food intake, contraceptive use for delaying menstruation for societal duties, unsafe living conditions, improved healthcare access, and shifting attitudes toward its naturalness, though some still link it to Chhaupadi. Therefore, this study emphasizes raising awareness about safer homestays during menstruation and improving economic opportunities in these areas to meet basic needs. Keywords: Chhaupadi; ethnography; inclusion; sinful.